STRATEGI KOMUNIKASI PEMASARAN DINAS PARIWISATA DAN KEBUDAYAAN KOTA PARIAMAN DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI PANTAI GANDORIAH - Rozi, Rahmat; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Gandoriah Beach is a leading tourist spot and visited by many tourists when visiting. Department of Tourism and Culture Pariaman City makes the tourism sector to increase APBD because this city is a new city formed than the city in West Sumatra. In increasing the number of visitors it takes an effective marketing communication strategy to create attraction. The purpose of this research is to know the segmentation, targetting, and positioning of Tourism and Culture of Pariaman City in increasing tourist visit at Gandoriah Beach attraction, to know the application of marketing communication elements done by Tourism and Culture of Pariaman City, to know the factors inhibiting factors in implementing marketing communications strategies. This study used qualitative research methods. Subjects in this study consisted of six subjects as an informant research through purposive techniques. Data collection techniques are grouped into three parts, namely: observation, interview and documentation. Data analysis techniques in this study using interactive data model Miles and Hiberman. The validity check of data using optin and triangulation extension techniques. The results showed that the marketing communication strategy undertaken by the Department of Tourism and Culture Pariaman City is by determining segmentation, targetting, and positioning thus facilitate in increasing tourist visits. The form of promotion that is done by using some media is event, booklet, social media, website, and brosur. Some of the inhibiting factors in carrying out marketing communication strategy by Tourism and Culture Office of Pariaman City is the absence of cooperation with third party or private in managing Gandoriah Beach attractions, and the minimum budget cost in promotion by local government. Keywords: Marketing communication strategy, promotion, Gandoriah Beach